Qualitative and Quantitative Study on Students’ Critical Thinking of Conceptual E-Scaffolding in Blended Learning Context - Mardikaningsih, Agusti; Kurniasari, Praharisti; Pradipta, Anangga (Journal International Inspire Education Technology, 2024)
Critical thinking ability is one of the rational thinking capabilities that is highly required by students in solving problems or delivering an idea. In fact, however, students’ critical thinking skill is still categorized as low according to the previous studies. One feasible alternative to be done in developing students’ critical thinking ability is implementing electronic-based scaffolding. For that reason, there should be research to examine conceptual e-scaffolding in blended learning on Problem-Based Learning (PBL) model to observe the first semester students’ critical thinking ability at IKIP Budi Utomo Malang. This study employed mixed-methods with explanatory research design. The experimental group was given conceptual e-scaffolding treatment in blended learning on Problem-Based Learning model and the control group did not receive any additional treatment. For both experimental and control groups, the research subject was the students in the first semester at IKIP Budi Utomo Malang. As there were two research groups, 46 students belonged to the control group. The instruments utilized in this research were pre-test and post-test. The pre-test consisted of 18 multiple choice items with reliability coefficient of 0.735 and critical thinking post-test consisted of 14 essay question items with reliability coefficient of 0.762. In addition, semi-structured interview and think aloud guidelines were used. Quantitative data were obtained from the distribution of pre-test and post-test items. Meanwhile, qualitative data were retrieved from semi-structured interview and think aloud. The quantitative data were then analyzed using ANACOVA parametric analysis while the qualitative data were analyzed using path analysis model. The research findings indicated that: 1) the critical thinking ability of students who studied with conceptual e-scaffolding in blended learning on Problem-Based Learning was higher than those who studied with conventional method, 2) the implementation of conceptual e-scaffolding in the form of link map in Problem-Based Learning model influenced positively towards students’ critical thinking ability. This was reflected from the behavior and the way of thinking of students belonged to the experimental group indicating critical thinking ability development during the learning process. Furthermore, conceptual e-scaffolding in the form of link map helped the students to obtain information easily and utilized it in understanding concepts in geometrical optic material.